Evaluation of Microbial water quality of selected swimming pools in Kuching, Sarawak - Wong, Sin Siong (University Malaysia Sarawak, UNIMAS., 2013)
Swimming pool has a high probability of becoming a transmitter of foodborne or waterborne diseases among users. Microbial water quality is assigned as monitor to the safety of consumers using the pool with the lowest chance of infection. UNIMAS Competition Pool, Boulevard Kids Recreational Pool and MBKS Public Swimming Pools were selected as study site for the microbial water quality whereas Escherichia coli and Vibrio cholera are selected as contamination indicator of swimming pool water. Spread plate technique was used to enumerate the microbial distribution. Biochemical tests were also conducted to confirm the presence of the indicator bacteria. PCR was conducted for confirmation test of V. cholerae. E. coli was found to be positive in 3.57% of water samples from UNIMAS with 1.888 × 104 CFU/mL, 3.33% of water samples from Boulevard with 1.718 × 108 CFU/ mL and 2.78% from MBKS with 7.900 × 108 CFU/mL.However, the result does not affect the safety of all the swimming pools. There was no V. cholerae found in all water samples obtained in Kuching.Physiological parameters did not showed significant relationship with the microbial indicators distribution in water samples.